Assessing the Potential Role of Open Data in South African Environmental Management - Adams, Rachel; Adeleke, Fola (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2016)
This study explores the possibilities for open data as a knowledge governance mechanism that could benefit environmental management in South Africa. The authors consider the potential benefits of open data in support of public participatory governance modalities, and the legislative frameworks and Constitutional Court stance in South Africa in support of the right of access to information and proactive disclosure of environmental information. The article also looks at potential barriers to effective use of open data in South Africa. The authors find that effective deployment of open data as a means to support participatory environmental governance will require a dedicated South African open data legal instrument, as well as political will to compile the necessary data, and steps to ensure meaningful citizen data access and use.
Keywords: open data, environmental management, participatory governance, access to information, knowledge governance, South Africa